Projections of future land use changes: Multiple scenarios-based impacts analysis on ecosystem services for Wuhan city, China - Wang, Ying; Li, Xiangmei; Zhang, Qi; Li, Jiangfeng; Zhou, Xuewu (Ecological indicators, 2018)
•Ecological land to urban land continues to dominate land use changes in Wuhan City.•Built-up land grows fast near major residential areas and along transport lines.•Projected land use changes in Wuhan would lead to declines in ecosystem services.•A tool to assess ecosystem service trade-offs arise from land use changes is proposed. Urbanization alters the supply of ecosystem services that are vital for human well-being. The loss of ecosystem services is particularly challenging in rapid urbanization areas where economic development needs to consume substantial natural resources. The quantitative and spatial optimization of land use provides an effective tool for rationally allocating land use structure and pattern to ensure the provision of expected ecosystem services. In this paper, we combine the Multi-Objective Programming and the Dyna-CLUE model to project land use changes in 2030 for Wuhan city under three scenarios, i.e., Business As Usual (BAU), Rapid Economic Development (RED), and Ecological Land Protection (ELP). The coupled model that integrates “top-down” and “bottom-up” processes is capable of obtaining the optimized land use patterns under different scenarios and examining the potential impacts of land use changes on ecosystem services in a spatially explicit way. We find that built-up land will continue its remarkable growth during 2015-2030 under the BAU scenario (grows by 96%) at the expense of ecological lands (decreases by 18%). Meanwhile, the predicted losses of ecological lands are 11% and 6% under the RED and ELP scenarios, respectively. Projected land use changes result in varying magnitudes of declines in ecosystem service values for BAU (11%), RED (6%) and ELP (2%) scenarios from 2015 to 2030. The ELP scenario, which incorporates ecological protection policies and spatial restrictions, plays a positive role in altering land use trends and mitigating ecosystem degradation. Finally, we establish an ecosystem service value change matrix to explain how interactions between land use types give rise to trade-offs among multiple ecosystem services. We find that conversions between ecological land use types can trigger trade-offs among ecosystem services, but the conversion from ecological lands towards urban land leads to a net loss of all individual ecosystem services. By linking land and ecological systems, the coupled modeling framework in this study can be useful for obtaining optimal ecosystem-based land use allocation strategies and provide scientific support for sustainable land use management.